WFS1 functions in ER export of vesicular cargo proteins in pancreatic β-cells - Linlin Wang (Nature Portfolio, 2021)
The role of cargo receptors in proinsulin export from the ER is unclear. Here, the authors identify the WFS1 protein, which is mutated in Wolfram syndrome and associated with diabetes, as an ER to Golgi cargo receptor required for normal insulin processing and secretion.